2008
DOI: 10.1002/pts.819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre‐treatment with carbon monoxide and film properties on the quality of vacuum packaging of beef chops

Abstract: Beef chops (longissimus dorsi) were pre-treated with 5% carbon monoxide (CO) − 95% N 2 for 24 h, vacuum packed in thermo-contractile bags and stored at 0 ± 2°C. Shelf life, as determined by the viable aerobic bacterial load, was 11 weeks. Vacuum-packed chops with heat-contractile fi lm produced a smaller drip loss, had a more intense red colour and higher colour stability under storage than chops with non-heat-contractile fi lm. Chops pre-treated with CO were redder during all the storage period than controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
(29 reference statements)
4
11
0
Order By: Relevance
“…All the samples started with the microbial count of about 4.3 log 10 (CFU/g), and achieved the highest counts ranging between 6.1 and 6.6 log 10 (CFU/g) after 21 days of storage. Similar changes in the growth of microorganisms during storage were observed in Vac beef steaks after the exposure to 5% CO by Aspé et al (), as well as by Sørheim et al () in steaks and by Lavieri and Williams () in ground beef packaged in a 0.4% CO‐MAP.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…All the samples started with the microbial count of about 4.3 log 10 (CFU/g), and achieved the highest counts ranging between 6.1 and 6.6 log 10 (CFU/g) after 21 days of storage. Similar changes in the growth of microorganisms during storage were observed in Vac beef steaks after the exposure to 5% CO by Aspé et al (), as well as by Sørheim et al () in steaks and by Lavieri and Williams () in ground beef packaged in a 0.4% CO‐MAP.…”
Section: Resultssupporting
confidence: 78%
“…This packaging allows for increasing the purchase desire of consumers, it can also be perceived as safer than CO‐MAP, due to the lack of the lengthy exposure to a potentially dangerous gas in the package. Additionally, our finding showed that considerable improvement in the color of beef samples was possible using 0.5% CO, and thus it is not necessary to use high concentrations of carbon monoxide before Vac such as 5% CO or 100% CO used in other studies (Aspé et al, ; Brewer et al, ; Jayasingh et al, ).…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…Beef pretreated with 5% CO:95% N 2 for 24 h before VP was redder than controls without VP. Heat shrinking of the VP resulted in lower drip loss, higher color stability and more intense red color than non-heat-shrunk packaging (Aspé et al ., 2008). Beef steaks in MAP with 0.2% CO and 30% CO 2 had the highest preservation of color and odor while steaks in 0.4% CO were regarded by panelists to have an 'artificial' color and color stability decreased with storage in 21% O 2 (Venturini et al ., 2010).…”
Section: Quality Improvement Through Packagingmentioning
confidence: 97%